Short and Medium Latency Responses in Participants With Chronic Ankle Instability - Sousa, Andreia S. P. (2019)
Context:  The determinant role of medium latency responses (MLRs) during compensatory postural adjustments in postural stability and the lack of clarity about the mechanisms behind chronic ankle instability (CAI) sustain the hypothesis that these postural responses are impaired in this condition. However, to the best of our knowledge, no authors have assessed MLRs in patients with CAI; most of the research regarding compensatory postural adjustments has been directed at the timing of short latency responses (SLRs). Objective:  To evaluate bilateral compensatory postural responses, including SLRs and MLRs, in response to a unilateral simulated ankle-sprain mechanism in participants with CAI. Design:  Case-control study. Setting:  Laboratory. Patients or Other Participants:  Twenty-four participants with CAI and 20 controls. Intervention(s):  Bilateral electromyography of the peroneus longus (PL), peroneus brevis, tibialis anterior (TA), and soleus (SOL) muscles was collected during a unilateral sudden-inversion perturbation (30°). Main Outcome Measure(s):  Muscle-onset activations and magnitudes of SLRs and MLRs in the support and perturbed positions. Results:  Participants with CAI showed (1) later-onset activation of the TA and SOL in the uninjured limb and bilateral decreases in the magnitude of the TA MLR in the support position, (2) increased magnitude of the PL MLR in the uninjured limb in the support and perturbed positions, and (3) increased magnitude of the PL SLR and MLR in the injured limb in the perturbed position. Conclusions:  Chronic ankle instability was associated with later TA and SOL activation in the uninjured limb and bilaterally decreased magnitude of the TA MLR in the support position.